Developing teachers' telecollaborative competences in online experiential learning. (February 2017) - Vinagre, Margarita
Abstract: In this paper we aim to investigate the development of the collaborative competences that teachers require when engaging in telecollaborative projects. In order to do so, we explore the data gathered from a group of teachers who were trained online to become future telecollaborative teachers. Participants carried out a series of tasks that included reading and reviewing articles on telecollaboration and implementing a virtual exchange. Quantitative and qualitative analyses were performed on the data gathered from a forum, wiki and answers to an end-of-course questionnaire. Results suggest that teacher training through modeling and exploratory practice may help teachers acquire the conceptual and procedural knowledge and skills (competences) required by the telecollaborative teacher. However, in order to develop procedural competences, teachers need to engage in experiential learning following a linear process that not only facilitates an understanding of what online collaboration entails, but also provides them with hands-on-experience and encourages them to reflect on the complexity of the collaborative process.